2014
DOI: 10.1371/journal.pone.0085037
|View full text |Cite
|
Sign up to set email alerts
|

Docosahexaenoic Acid Decreases Pro-Inflammatory Mediators in an In Vitro Murine Adipocyte Macrophage Co-Culture Model

Abstract: Paracrine interactions between adipocytes and macrophages contribute to chronic inflammation in obese adipose tissue. Dietary strategies to mitigate such inflammation include long-chain polyunsaturated fatty acids, docosahexaenoic (DHA) and eicosapentaenoic (EPA) acids, which act through PPARγ-dependent and independent pathways. We utilized an in vitro co-culture model designed to mimic the ratio of macrophages:adipocytes in obese adipose tissue, whereby murine 3T3-L1 adipocytes were cultured with RAW 264.7 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 45 publications
7
51
0
Order By: Relevance
“…d) agrees with conclusion of De Boer et al. () that transcriptionally active NF‐ κ B subunit may not be a useful endpoint to measure the inflammatory status of cells.…”
Section: Discussionsupporting
confidence: 90%
“…d) agrees with conclusion of De Boer et al. () that transcriptionally active NF‐ κ B subunit may not be a useful endpoint to measure the inflammatory status of cells.…”
Section: Discussionsupporting
confidence: 90%
“…The fish oil‐derived eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) strongly promote the alternative activation of macrophages. In vitro treatment of macrophages with EPA and DHA results in an M2‐like phenotype, exhibiting reduced pro‐inflammatory gene expression and increased anti‐inflammatory gene expression . We and others have shown that supplementation of mice with dietary fish oils reduced AT expression of pro‐inflammatory genes while increasing adiponectin expression.…”
Section: Mediators Of M2 Polarizationmentioning
confidence: 77%
“…It is likely that the FA affected the secretion of IL6 by resident macrophages within the undifferentiated SVC used in this study (Fain, ). PAM has also been shown to induce secretion of IL6 from murine adipocytes (Chakrabarti et al, ) and adipocyte cell line (Ajuwon & Spurlock, ) as well as human endothelial cells (Staiger et al, ), while DHA decreased IL6 secretion from human subcutaneous adipocytes differentiated in culture (Bjork et al, ) and from 3T3L‐1 cells (De Boer, Monk, & Robinson, ). It is possible that PAM and EPA affected secretion of IL6 from preadipocytes and endothelial cells within the undifferentiated SVC in this study as well, contributing to the overall secretion of IL6 from the SVC in this study.…”
Section: Discussionmentioning
confidence: 99%